Visual hierarchy in poster design / Nur Afiqah Faizalazmi @Faizul Hazmi - Faizalazmi @Faizul Hazmi, Nur Afiqah (Faculty of Art and Design, 2020)
Visual is something to see, and it is thought to be the type that most people rely on, including signs, graphic designs, films, typography, photography, and countless other examples. Something should also be explained (Cambridge Dictionary, 2019). Whereas, Visual Design seeks to form and improve the user experience by taking into account the impact of graphics, imagery, typography, space design, and color on product usability and aesthetic appeal. The visual design includes several concepts to help designers accomplish this, including unity, Gestalt properties space, hierarchy, balance, contrast. size, dominance and similarity (Hovadhanakul,2019). visual design is not just about creating nice-looking visuals or imagery, and it ‘show to convey product concepts though presenting a curated visual design interface to the audience (Hovadhanakul.2019). Designers need to send meaning and message to the viewer. It then works to turn the definition into visual elements and then organise the details so that the desired result that conveys the meaning and message can be achieved. In terms of understanding how to design a poster, hierarchy is just as important as visual. Hierarchy is the most crucial element to be seen when making a poster design that meant hierarchy is the use of visual information to indicate significance in a structure or presentation.